Young Adults Rehabilitation Needs and Experiences following Stroke (YARNS): A review of digital accounts to inform the development of age‐appropriate support and rehabilitation. (10th October 2021) - Holloway, Aisha; Chandler, Colin; Aviles Reinso, Lissette; Clarissa, Catherine; Putri, Arcellia; Choi, HyeRi; Pan, Jo‐Fan; Mitra, Udita; Hewitt, Jonathan; Cluckie, Gillian; Smart, Alison; Noble, Helen; et al.
Abstract: Aims: To explore younger adults' experiences of stroke rehabilitation to inform practice, education and future health policy. Design: Qualitative analysis of digital and other media sources on public platforms. Methods: Between March and June 2020, the experiences of younger adult stroke survivors aged 18 to 45 at the time of the stroke were collected. Data were gathered from publicly available sources, including social media, and from English‐speaking users. In total, 117 accounts from 103 participants were identified from films, autobiographical books, blogs, websites, videos, Twitter and Instagram. Data analysis followed narrative and multimodal analysis with a focus on rehabilitation needs. Results: Younger adult stroke survivors make sense of their experience by reflecting on how stroke has impacted their lives. Accounts reflected an emotional journey between the past self, the present self and evolving self, as well as associated challenges such as the impact on relationships and careers. The majority of accounts presented transitions as problematic, including the receipt of the initial diagnosis, or sometimes misdiagnosis, to returning home and achieving long‐term rehabilitation goals. Specialist stroke nurses were considered essential in the rehabilitation process. Conclusion: A complex process of recovery follows stroke for younger adult stroke populations. Challenges to the rehabilitation process need to be better understood and the role of nursing highlighted in future service provision. A series of age‐related challenges were highlighted that require attention to improve the care and support offered. Impact: This article informs clinicians, educators, and policymakers of the age‐related needs of young adult stroke survivors. Focusing on the individual and the development of age‐appropriate person‐centred stroke care is important. The study highlights the role of stroke nursing and challenges the current policy focus on older stroke populations as well as arguing for greater awareness of age‐appropriate stroke rehabilitation in younger adults following stroke.